Association between SNPs of Circulating Vascular Endothelial Growth Factor Levels, Hypercholesterolemia and Metabolic Syndrome - Ali Salami; Said El Shamieh (Medicina, 2019)
Background and Objectives: Four single nucleotide polymorphisms (SNPs); rs6921438 and rs4416670 in LOC100132354-C6orf223, rs6993770 in ZFPM2, and rs10738760 in VLDLR-KCNV2 were reported to explain up to 50% of the heritability of vascular endothelial growth factor circulating levels. These SNPs were also studied for possible associations with circulating lipid levels in supposedly healthy European individuals and in a limited number of Iranian individuals with metabolic syndrome. To go further, the association of those four SNPs with plasma lipid parameters, hypercholesterolemia and metabolic syndrome (MetS) was assessed. Materials and Methods: A cross-sectional study was conducted on 460 individuals chosen from the general population. Demographic and clinical data were collected and DNA was extracted and genotyped using Kompetitive allele specific PCR (KASP™). A meta-analysis followed, combining our participants with the Iranian individuals (n = 336). Results: Whereas rs10738760 was associated with total cholesterol (Tchol) (p = 0.01), rs6993770 showed significant associations with both Tchol and low-density lipoprotein cholesterol (LDL-C) levels (p = 0.007 and p = 0.01 respectively). Using a multivariate logistic regression model adjusted for different confounding factors, we found that rs6993770 was associated with hypercholesterolemia, specifically high Tchol (p = 0.01) and LDL-C levels (p = 0.01). Furthermore, rs10738760 was positively associated with the risk of MetS in these individuals (p = 0.02) and in the meta-analysis (OR = 1.67, p = 0.01). Conclusion: Our results suggest that whereas rs6993770 in ZFPM2 was positively associated with hypercholesterolemia, rs10738760 (VLDLR-KCNV2) has a possible implication in MetS in two Middle Eastern populations.